A double-blind, crossover, randomized dose-comparison trial of granisetron for the prevention of acute and delayed nausea and emesis in children receiving moderately emetogenic carboplatin-based chemotherapy - (:unkn) unknown (SPRINGER, 2007)
Background Granisetron is a safe and effective prophylaxis for nausea and vomiting associated with moderate to highly emetogenic chemotherapy. Few trials have been conducted to determine the optimal effective dose of granisetron in children with cancer. The objective of this report was to compare two doses of granisetron in patients with optic pathway tumors receiving moderately emetogenic doses of carboplatin. Patients and methods In this double-blind, crossover, randomized study, antiemetic efficacy and tolerability of two dose levels (10 and 40 mu g/kg) of granisetron in the prevention of acute and delayed nausea/emesis were compared in children and young adults. A total of 18 patients (13 boys) aged 1-23 years (median 7.7 years) treated with a moderately emetogenic dose of carboplatin were randomly assigned to receive either 10 or 40 mu g/kg of slow granisetron intravenous (i.v.) infusions at alternating cycles of chemotherapy in a blinded fashion until the end of the study period or until their chemotherapy regimen ended. In this way, the patients acted as their own controls. Results Patients in the granisetron 10 and 40 mu g/kg groups received 104 and 121 cycles of chemotherapy, respectively. There was no significant difference in antiemetic efficacy in terms of nausea and emesis between the dose groups in the first 5 days of chemotherapy. The treatment was well tolerated. Conclusion We conclude that granisetron 10 and 40 mu g/kg have comparable efficacy in controlling carboplatin-induced acute and delayed nausea/emesis and is well tolerated in children and young adults.
Keywords: granisetron; antiemetic; efficacy; chemotherapy; dose comparison; RECEPTOR ANTAGONISTS; ANTIEMETIC THERAPY; PROPHYLAXIS; EFFICACY; CANCER; DEXAMETHASONE; SAFETY